South African student leaders' role experience through social dream drawing: A driver of compassion - Neo Pule; John Gibney (Frontiers in Psychology, 2023)
IntroductionCompassion can be viewed as a central gluing agent for the soul. Coupled with companionship toward a unique quality of listening, we call this companionate listening. South African student leaders' role is central to the decolonization and transformation of higher education based on the legacies founding these institutions. As such, a humanized practice that is centered on more emotional or virtue-embodied approaches than the traditional lens has been sought. This lens offers avenues for innovative, creative, and inclusive perspectives that promote compassion, social justice, and democracy.MethodsTo extend existing conceptualizations of compassion, this research uses social dream drawing to attain “companionate listening” as a means of exploring communication as “exquisite” empathy. Through psychoanalytic theory, companionate listening is theorized from observing the value of social dream-drawing research with South African student leaders.ResultsThe drawings show how assuming leadership roles re-ignites feelings and dream images of complex political, historical, social, cultural, and psychological South African intersections that emerge during South African student leadership.DiscussionIt is, therefore, concluded that innovative and inclusive research agendas into new horizons of forms of compassion, like social dream drawing in this research, are necessary within South African student leadership. Accordingly, through social dream drawing, compassionate listening facilitates a process of emotional growth toward an integrated self and group. This is because dreams allow the human capacity for connections that open space for compassion, enabling the feeling of relatedness and connection for student leaders that leads to the more impactful transformation of South African institutions.